Investigation of elastic properties, anisotropy and edge dislocations of Ti3Al with tensor theory and bond matrix model. (August 2022) - Fu, Hongzhi
Abstract: The anisotropic elastic properties, topology structure of brittleness and the transformation of edge dislocations in Ti3 Al are studied in detail based on Bond matrix model and the tensor theory of elastic media. The results contain remarkably complex three-dimensional variations in the anisotropy and brittleness with angular distribution. The feature of elastic properties and brittleness in Ti3 Al is affected by the elastic anisotropy of the lattice. Their topology surfaces give insights into the relationship between elastic anisotropy and brittleness. It is helpful to understand the dislocation field through comparative study of the edge dislocation in the dislocation coordinate system and crystal coordinate system with tensor theory as well as the Bond matrix model. Graphical abstract: 3-D Brittleness of Ti3 Al. Image 1 Highlights: The 3D-brittleness in Ti3 Al. The elastic anisotropy affects the brittleness in Ti3 Al. The universal approach for transformation of stress and strain field between the dislocation coordinate system with Bond matrix model.